"I've Already Lived Like There's a Pandemic" : A Grounded Theory Study on the Experiences of People with a Mobility Disability - Yang, Michelle (Université d'Ottawa / University of Ottawa, 2022)
BACKGROUND: It is widely documented that people with a mobility disability are at increased risk of severe illness, morbidity, or mortality following a disaster. However, disaster risk is multifactorial and not simply a result of underlying conditions. There is a need to examine contributors to dis- ability experiences during a pandemic, and strategies to account for these in pandemic response. METHODS: Using grounded theory methodology, we employed iterative, inductive coding, and constant comparative methods. Sixteen people with a mobility disability from Ontario and Quebec, Canada, participated in 1-hour qualitative interviews (ages 20-86). Participants' disability etiology included stroke, multiple sclerosis, amputations, and other. RESULTS: The pandemic was a source of dis-ability for the whole population, making disability disparities more noticeable and highlighting the role of adaptive capacity in disaster resilience. Although COVID-19 compounded existing barriers faced by people with a mobility disability, participants were able to mobilize their assets (i.e., individual capacity, mobility assists, etc.), empowering them to take action to maintain autonomy. When the general population experienced barriers to social connection, adaptations to support resilience were at the forefront of policy decisions. New solutions, including digital infrastructure, demonstrated the potential to diminish existing barriers by providing accommodations to meet the accessibility needs of people with disability, especially for regular healthcare provider contact. CONCLUSION: The COVID-19 pandemic is an opportunity to break the cycle perpetuating health-related inequities. Pandemic planning, response, and recovery can be reformed toward disability-inclusiveness with systemic changes focused on human rights and physical and psychosocial needs of people with a mobility disability.
Keywords: Mobility; Disability; Pandemic response; Grounded Theory; Disasters; Resilience